Gamification in Learning and Education Enjoy Learning Like Gaming - Kim, Sangkyun (Advances in Game-Based Learning,, 2018)
This book explores the theoretical foundations of gamification in learning and education. It has become increasingly difficult to engage and motivate students. Gamification not only makes learning interesting, but also allows game players to solve problems and learn lessons through repeated attempts and failures. This "positive failure" can motivate students to attempt a difficult mission. Chapters in this volume cover topics such as the definition and characteristics of gamification, gamification in learning and education, theories, research on gamification, framework, strategy, and cases.